The effects of instructional and motivational self-talk on vertical jump performance and kinematics - Muhammad Hakim Mustadza (2019)
Background: Numerous studies have examined the effects of self-talk on tasks of varying nature. However, few have objectively examined tasks that emphasize muscular power. Purpose: To investigate the effects of instructional, motivational and combined (instructional and motivational) self-talk on jump height (JH) and rate of force development (RFD) in the countermovement vertical jump (CMJ). Methods: 12 male (24.3±0.9 years, 1.75±0.06 m, 68.7±6.02 kg) and 12 female (22.8±2.1 years, 1.59±0.05 m, 55.3±6.02 kg) university students performed 4 CMJ’s with an unloaded 10kg barbell, 3 minutes apart, on a force plate set at 1000-Hz sampling frequency. Before each trial, participants engaged in 1 of 4 counterbalanced conditions. After each trail, participants were put through a manipulation check to assess adherence to self-talk conditions. Results: One-way repeated measures MANOVA for JH and RFD revealed no significant differences between conditions, F(6,136) = 1.644, p = .140, ηρ² = .068. Manipulation check results revealed low participant engagement (< 60%) during the control condition and low perceived usefulness of self-talk cues for motivational (66.7%) and combined (41.7%) self-talk. Conclusion: Results indicate that self-talk does not lead to significant differences in JH and RFD during the CMJ.